2004
DOI: 10.1007/s11920-004-0078-9
|View full text |Cite
|
Sign up to set email alerts
|

Patient and family attitudes toward schizophrenia treatment

Abstract: Patient and family member attitudes toward illness, psychopharmacologic and nonpharmacologic treatments in schizophrenia, as well as their attitudes toward psychiatric research are reviewed here. The authors' recent work investigating patient and family member attitudes toward illness, medication, and a new method of receiving medication via surgical implants is also presented. The authors highlight the importance of understanding patient attitudes so that individual treatment plans and new treatments for schi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Although research in youth samples suggests that close others’ therapy attitudes can influence treatment engagement, response, and drop out, there has been little research on this topic, especially for people with anxiety and related disorders. Treatment acceptability research has surveyed parents of youth with ADHD (Berger et al, 2008 ) and family members of those with schizophrenia (Irani et al, 2004 ), finding that family members are supportive of pharmacological interventions for mental health treatment. Tarnowski and colleagues ( 1992 ) found that parents prefer therapy over medication for the treatment of childhood depression, and similar findings have been reported for childhood anxiety (Brown, Deacon, Abramowitz, Dammann, & Whiteside, 2007; Chavira et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although research in youth samples suggests that close others’ therapy attitudes can influence treatment engagement, response, and drop out, there has been little research on this topic, especially for people with anxiety and related disorders. Treatment acceptability research has surveyed parents of youth with ADHD (Berger et al, 2008 ) and family members of those with schizophrenia (Irani et al, 2004 ), finding that family members are supportive of pharmacological interventions for mental health treatment. Tarnowski and colleagues ( 1992 ) found that parents prefer therapy over medication for the treatment of childhood depression, and similar findings have been reported for childhood anxiety (Brown, Deacon, Abramowitz, Dammann, & Whiteside, 2007; Chavira et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, compared to the general population, psychiatric patients and their relatives have been found to have slightly more positive attitudes towards psychotropic medications 191,192,193,194,195, and some studies report that satisfaction with this form of treatment is high 196,197,198. Previously hospitalized patients showed more positive attitudes towards psychiatric treatment 199,200,201.…”
Section: Results Of the Review Of Knowledgementioning
confidence: 99%